2009
DOI: 10.1249/jsr.0b013e3181ae8959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Dietary Flavonoid Quercetin Upon Performance and Health

Abstract: There is increased interest among such diverse groups as the military, athletes, and the aged for novel plant-derived dietary supplements to enhance performance and maintain/improve health. Quercetin, a flavonoid found in fruits and vegetables, has unique biological properties that are likely to improve mental/physical performance and reduce infection risk during intense exercise. These properties include antiinflammatory, antioxidant, and psychostimulant activity, as well as the ability to stimulate mitochond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
143
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(146 citation statements)
references
References 24 publications
2
143
0
1
Order By: Relevance
“…Bae et al demonstrated that quercetin-treated cancer cell lines showed enhanced susceptibility to NK cells through induction of NKG2D ligands. These effects were found to be caused by blocking of nuclear factor-kappa B and phosphatidylinositol 3-kinase pathways (Davis et al 2009;Bae et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Bae et al demonstrated that quercetin-treated cancer cell lines showed enhanced susceptibility to NK cells through induction of NKG2D ligands. These effects were found to be caused by blocking of nuclear factor-kappa B and phosphatidylinositol 3-kinase pathways (Davis et al 2009;Bae et al 2010).…”
Section: Discussionmentioning
confidence: 98%
“…It has been theorized that cancer risk reduction may be achieved by greater consumption of phytochemicalrich fruits and vegetables (Davis et al, 2009;Rinaldi et al, 2009). However, results of our research suggest that antioxidants can interfere and attenuate success of anticancer therapy so antioxidant intakes should be strictly controlled in the cancer diagnosed patients.…”
Section: Discussionmentioning
confidence: 99%
“…The final common pathway of kidney damage often involves inflammation and fibrosis [Fassett et al, 2011]. So, nutrients and bioactive compounds that can influence inflammation and have antioxidant activity, such as omega-3 polyunsaturated fatty acids, phytosterols and phenolic compounds [Davis et al, 2009;Rosenbaum et al, 2010], may be used in the adjuvant treatment of kidney diseases. Diets rich in fruits, vegetables and spices offer protection against the development of chronic diseases due to presence of such nutraceuticals [Brevik et al, 2011].…”
Section: Cisplatin (Cis-diamminedichloroplatinum II Cddp)mentioning
confidence: 99%